Mammary Paget Disease With Melanocytic Proliferation Mimicking Malignant Melanoma in situ: A Case Report - Rao, Shijia; Wang, Alun; Liu, Wei; Yin, Hongling; Li, Ji; Tsang, Lemuel Shui-Lun; Wu, Yuhui; Shi, Wei (Frontiers in Medicine, 2022)
Several cases of pigmented mammary Paget disease (PMPD) mimicking cutaneous malignant melanoma have been reported. In these cases, the tumor cells are colonized by melanocytes, indicated by the presence of a population of melanocytes staining for HMB-45 and S100. Here, we report a case of mammary Paget disease (MPD) which was misdiagnosed as melanoma in-situ due to the interpretation of the staining of melanocytic markers of S-100, Melan-A, and HMB-45. The tumor cells strongly expressed CK7 and GATA3, and a dual labeling showed negative PHH3 labeling for the melanocytes. Pathologists need to be aware of the caveat of colonization of melanocytes in Paget disease.